2001
DOI: 10.1159/000047443
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Deposition in the Aged Human Pineal Gland

Abstract: The purpose was to discover whether fluoride (F) accumulates in the aged human pineal gland. The aims were to determine (a) F–concentrations of the pineal gland (wet), corresponding muscle (wet) and bone (ash); (b) calcium–concentration of the pineal. Pineal, muscle and bone were dissected from 11 aged cadavers and assayed for F using the HMDS–facilitated diffusion, F–ion–specific electrode method. Pineal calcium was determined using atomic absorption spectroscopy. Pineal and muscle contained 297±257 and 0.5±0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 14 publications
1
52
0
3
Order By: Relevance
“…Therefore, F-induced modification of G-proteins could inhibit the release of testosterone, and since testosterone is essential for the initiation of spermatogenesis, this inhibition would eventually lead to low levels of testosterone, thereby impairing spermatogenesis [15,26]. It is reported that fluoride is known to accumulate in the pineal gland [27] and to inhibit the release of melatonin by the pineal gland [28]. Since melatonin has an anti-gonadotropic effect, it is conceivable that fluoride inhibition of melatonin indirectly but significantly increases the level of gonadotropins [29].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, F-induced modification of G-proteins could inhibit the release of testosterone, and since testosterone is essential for the initiation of spermatogenesis, this inhibition would eventually lead to low levels of testosterone, thereby impairing spermatogenesis [15,26]. It is reported that fluoride is known to accumulate in the pineal gland [27] and to inhibit the release of melatonin by the pineal gland [28]. Since melatonin has an anti-gonadotropic effect, it is conceivable that fluoride inhibition of melatonin indirectly but significantly increases the level of gonadotropins [29].…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, neste estudo, as concentrações de F na pineal dos animais Tratados não diferiram dos animais Controles. Esse resultado não condiz com o encontrado por Luke (2001), o qual observou concentração de F na glândula pineal de humanos, aproximadamente quatro vezes superior aos teores verificados nos ossos.…”
Section: Discussionunclassified
“…An accumulation of fluoride in the pineal gland has been identified in association with aging [145]. Excitotoxicity has been proposed as a central mechanism in fluoride toxicity, in part due to its ability to readily complex with Al to form AlF x complexes [146].…”
Section: Depression Alzheimer's and The Pineal Glandmentioning
confidence: 99%